Constitutional Dynamics and Judicial Autonomy in South Asia: A Comparative Study of Pakistan and its Neighbors - Aamir Khan; Dr Imran Naseem; Dr Muhammad Inamullah (Al Manhal Research Journal, 2025)
Constitution as supreme law of land and foundational document,outlines the fundamental principle, structure and power of a government. Judiciary derives its power and jurisdiction from the constitution. Constitutional dynamics play a critical role in shaping the judiciary’s role, power and function.In this research article we examine, that how constitutional dynamics influence the judicial autonomy in South Asia, with special focus on Pakistan and India. This study focuses on the influence that constitutional amendments have on judicial appointments, jurisdiction, independence in judiciary and the emerging role of the judiciary in the two countries. The research takes into account landmark constitutional verdicts, Eighteenth and Twenty-Sixth Amendments to the Constitution in Pakistan and India's basic structure doctrine with Three Judges Cases, respectively-which defined the independence of the judiciary. The study also delves into historical intervention by the military into Pakistan's judicial structure and its implications for democratic governance, in contrast with India, whose judiciary has maintained relative autonomy with continued challenges in striking a balance with powers of the executive and legislature. By taking comparative approaches, the effectiveness of judicial reform and the work of constitutional courts in safeguarding democratic principles are studied. From the findings, the discourse on judicial independence, constitutionalism, and governance could be pushed further in South Asia through recommendations in enhancing judicial transparency and institutional integrity of both countries.